EFFECT OF DIFFERENT AMBIENT FACTORS ON TEMPERATURE DISTRIBUTION IN THREE-PHASE INDUCTION MOTOR - Thamer Abdullah, Afrah; Majbel Ali, Amer (Journal of Engineering and Sustainable Development, 2020)
This paper adopted a thermal network method (TNM) based on Motor-CAD software for investigating of temperature distribution inside different parts of a totally enclosed fan cooled (TEFC), squirrel cage, three-phase induction motor, with taking ambient considerations like ambient temperature, altitude, relative humidity, and contamination into account. The thermal model of the test motor was done according to its design documents. The results obtained from Motor-CAD were verified by comparing it with that obtained from the finite element analysis taken from Flux2D software with a good agreement.